Answer: 2x-5y = -8 equation (1) multiply equation (2) by 2 and then subtract equation (1) from (2) step 2: 2x-8y = -14 2x-5y= -8 -3y= -6 now divide both sides by -3 we will get -3y/-3 = -6/-3 y = 2 now put y = 2 in anyone of the above equation we will get I am going to put in equation 1 2x -5(2) = -8 2x – 10 = -8 add 10 to both sides 2x -10+10 = -8+10 2x +0 = 2 or 2x= 2 now divide both sides by 2 we will get 2x/2= 2/2 x = 1 so x=1 and y= 2 Reply

Answer:2x-5y = -8 equation (1)

multiply equation (2) by 2 and then subtract equation (1) from (2)

step 2: 2x-8y = -14

2x-5y= -8

-3y= -6

now divide both sides by -3 we will get

-3y/-3 = -6/-3

y = 2

now put y = 2 in anyone of the above equation we will get

I am going to put in equation 1

2x -5(2) = -8

2x – 10 = -8

add 10 to both sides

2x -10+10 = -8+10

2x +0 = 2

or 2x= 2

now divide both sides by 2 we will get

2x/2= 2/2

x = 1

so x=1 and y= 2